A survey of lay knowledge of autism spectrum disorder in Malaysia - Low, Hui Min; Lee, Lay Wah; Aznan Che Ahmad,; Eni Eliza Ghazali,; Tan, Phaik Kah; Lee, Ann Sien Sut (Penerbit Universiti Kebangsaan Malaysia, 2021)
Today, increasingly more people worldwide are aware about Autism Spectrum Disorder (ASD). However, their actual knowledge about ASD is yet unknown. The lack of knowledge about ASD is especially apparent among the lay people in the community. In this study, the lay knowledge of ASD was investigated using a brief survey involving a community sample in Malaysia. The survey findings revealed that the vast majority of the respondents could relate to ASD as a type of learning disability. However, they were less familiar with the diagnostic features and remedial needs of ASD. They also reported limited knowledge about the social communication and language deficits of ASD. Another noteworthy finding was that the respondents reported different sources of obtaining ASD knowledge according to their demographic profiles (namely age, gender, education and occupation), which correspondingly led to variability in the type of knowledge they obtained. Together, the findings implied that content-specific ASD awareness programs through the right channels are warranted for optimizing efficacy in knowledge transfer and minimizing redundancy in existing ASD awareness campaigns. Increased lay knowledge on ASD will provide a public guardian ground for children with ASD to ensure that the challenges faced by them can be identified at an early age for optimizing the remedial outcomes.